Microwave assisted synthesis using catalysts on controlled pore glass carriers - Freitag, Janine; Hermann, Monika; Nüchter, Matthias; Ondruschka, Bernd; Schneider, Franziska; Stolle, Achim (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
Due to their beneficial features, TRISO®-controlled pore glass carriers are very well suited for the preparation of catalysts for application in technically important reactions, e.g., C–C-coupling processes of the Suzuki-reaction type or highly selective hydrogenations. We describe here the development of first experiments with an effective and sustainable catalyst system in microwave-assisted syntheses. An essential advantage of porous catalysts prepared using microwave conditions is their reusability after reaction for further processes. The results are promising as regards the inception of a scalable reaction system for application in synthetic reactions using microwave energy.
Optica Applicata, Vol. 35, 2005, nr 4, s. 745-752
Keywords: optyka; controlled pore glass; microwave energy; heterogeneous catalysis